2014
DOI: 10.4161/gmic.29330
|View full text |Cite
|
Sign up to set email alerts
|

The interplay between the gut microbiota and the immune system

Abstract: The impact of the gut microbiota on immune homeostasis within the gut and, importantly, also at systemic sites has gained tremendous research interest over the last few years. The intestinal microbiota is an integral component of a fascinating ecosystem that interacts with and benefits its host on several complex levels to achieve a mutualistic relationship. Host-microbial homeostasis involves appropriate immune regulation within the gut mucosa to maintain a healthy gut while preventing uncontrolled immune res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
108
1
6

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 179 publications
(115 citation statements)
references
References 97 publications
0
108
1
6
Order By: Relevance
“…Surprisingly, while a plethora of studies have focused solely on the impact of dust on eukaryotic cells, a limited number have attempted to characterize the effects of dust on bacteria. This is of significance since abnormal changes in normal bacterial flora have been linked to obesity, inflammatory bowel diseases, poor immune responses, sensitivity to allergens, dermatitis and, quite recently, reduced efficacy of anti-tumor treatments (Cao et al, 2014;Ferreira et al, 2014;Geuking et al, 2014;Iida et al, 2013;Khan et al, 2014;Kotzampassi et al, 2014;Lee and Lee, 2014;Robles Alonso and Guarner, 2013;Viaud et al, 2014a,b;Weyrich et al, 2015). One recent study sought to determine seasonal contributions to the toxicity of various PM components (including microbes) on a cultured mouse macrophage-like cell line (RAW 264.7 cells).…”
Section: Introductionmentioning
confidence: 97%
“…Surprisingly, while a plethora of studies have focused solely on the impact of dust on eukaryotic cells, a limited number have attempted to characterize the effects of dust on bacteria. This is of significance since abnormal changes in normal bacterial flora have been linked to obesity, inflammatory bowel diseases, poor immune responses, sensitivity to allergens, dermatitis and, quite recently, reduced efficacy of anti-tumor treatments (Cao et al, 2014;Ferreira et al, 2014;Geuking et al, 2014;Iida et al, 2013;Khan et al, 2014;Kotzampassi et al, 2014;Lee and Lee, 2014;Robles Alonso and Guarner, 2013;Viaud et al, 2014a,b;Weyrich et al, 2015). One recent study sought to determine seasonal contributions to the toxicity of various PM components (including microbes) on a cultured mouse macrophage-like cell line (RAW 264.7 cells).…”
Section: Introductionmentioning
confidence: 97%
“…The protective effects associated with these microbes are mediated by multiple mechanisms involving T cells, dendritic cells (DCs) and epithelial cells. Recent studies have suggested that commensal microbiota is actively involved in the development of adaptive immune responses by programming many aspects of CD4 + T cell differentiation [6].…”
Section: Introductionmentioning
confidence: 99%
“…A influência da microbiota intestinal sobre os demais sistemas pode ter consequências até a fase adulta, podendo manifestar-se através de alterações no metabolismo e da resposta imunológica. Tais modificações podem tornar o indivíduo mais resiliente ou mais suscetível ao desenvolvimento de psicopatologias (23)(24)(25). Aos três anos de idade, a flora intestinal começa a se estabilizar e assume um padrão semelhante à microbiota do indivíduo adulto.…”
Section: Resultados E Discussão a Flora Intestinalunclassified